2014
DOI: 10.1002/asl2.488
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tropical instability waves‐induced SST forcing on the atmosphere in the tropical Pacific, evaluated using CAM5.1

Abstract: A new version of the Community Atmospheric Model, CAM5.1, is used to quantify the impacts of tropical instability waves (TIWs)-induced sea surface temperature (SST TIW ) forcing on the atmosphere over the central-eastern tropical Pacific. Two CAM5.1-based simulations are performed, a control run in which monthly mean climatological SST (SST clim ) field is prescribed as a surface boundary condition, and a perturbation run in which daily varying SST TIW field explicitly extracted from satellite data is superimp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, the study focuses on ocean response, and has not investigated the atmospheric response to the coupling. The atmospheric response to fronts and eddies has been an area of rich studies in many regions, such as the Aughlas current [21] , the Gulf Stream [24] , the eastern Equatorial Pacific [8] , and so on. The global atmospheric response to the scheme will be explored in the future.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the study focuses on ocean response, and has not investigated the atmospheric response to the coupling. The atmospheric response to fronts and eddies has been an area of rich studies in many regions, such as the Aughlas current [21] , the Gulf Stream [24] , the eastern Equatorial Pacific [8] , and so on. The global atmospheric response to the scheme will be explored in the future.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The sea surface temperature (SST) frontal influences on surface winds and wind stress at oceanic mesoscale have been well documented [1][2][3][4][5][6][7][8][9][10] . Satellite scatterometer measurements, in-situ observations and numerical models all reveal that surface wind is higher over warm water and lower over cold water near a SST front.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that wind stress is modified over regions with large SST gradients (e.g., Chelton et al, 2004;Chelton & Xie, 2010;K.-A. Park et al, 2006;Small et al, 2008;R.-H. Zhang et al, 2014). Due to the low resolution in current POP2, SST fronts simulated will be smoothed out, and thus, the effect of SST gradient on wind stress might be underestimated.…”
Section: A Modified Air-sea Flux Parameterizationmentioning
confidence: 97%
“…Park et al, 2006; Small et al, 2008; R.‐H. Zhang et al, 2014). Due to the low resolution in current POP2, SST fronts simulated will be smoothed out, and thus, the effect of SST gradient on wind stress might be underestimated.…”
Section: Overview Of the Ciesm Development Effortsmentioning
confidence: 99%